Novel route to enhance the thermo-optical performance of bicyclic diene photoswitches for solar thermal batteries - Sangolkar, Akanksha Ashok; Kadiyam, Rama Krishna; Pawar, Ravinder (Beilstein Journal of Organic Chemistry, 2024)
Harnessing solar energy by employing chemical photoswitches in molecular solar thermal (MOST) energy storage systems is a topic of appealing research interest. However, incorporating all the features desired for an ideal MOST system in a single photoswitching couple is challenging. Inspired by experimental synthesis, herein we report our attempt to enhance both the thermochemical and photophysical properties in a single-bridged bicyclic diene (BBD)-based photoswitch by elongating the unsaturated bridge with different heteroatomic units. To elucidate the best elongation unit, the energy storage capacity and the TBR barriers were accounted using the DLPNO-CCSD(T) and (8,8)-CASPT2 methods, respectively. The photophysical properties including the absorption onset, excitation wavelengths, and the absorption intensities were extensively investigated with the time-dependent calculations. The result provides information on the most versatile solvent to exhibit the best photoswitching behaviour which is beneficial for real-life energy storage applications. Additionally, the stability and reversibility of the photoswitching system with elongated unsaturated bridges have also been assessed. By means of the studied modification, the storage energy of 158.57 kJ/mol, energy storage density of 1.48 MJ/kg, TBR barrier of 136.36 kJ/mol, and the absorption onset of 305.00 nm is achieved in acetonitrile. These values are substantially higher when compared with the storage energy (96.06 kJ/mol), energy storage density (1.04 MJ/kg), and TBR barrier (121.76 kJ/mol) of prototype NBD/QC in the gas phase. The outcomes render useful insights into the stability and properties of bicyclic diene-based photoswitches having elongated unsaturated bridges and indeed paves the way for the rational design of practical MOST systems.
Keywords: bridged bicyclic diene (BBD); molecular solar thermal (MOST) energy storage; reversible photoswitches; unsaturated bridge elongation